2015
DOI: 10.1103/physrevd.91.094033
|View full text |Cite
|
Sign up to set email alerts
|

Single-spin asymmetries inWboson production at next-to-leading order

Abstract: We present an analytic next-to-leading order QCD calculation of the partonic cross sections for single-inclusive lepton production in hadronic collisions, when the lepton originates from the decay of an intermediate electroweak boson and is produced at high transverse momentum. In particular, we consider the case of incoming longitudinally polarized protons for which parity-violating single-spin asymmetries arise that are exploited in the W boson program at RHIC to constrain the proton's helicity parton distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
(183 reference statements)
2
14
0
Order By: Relevance
“…There are also some theoretical studies on A W ± L based on available extractions or parametrizations of quark helicity distributions [33][34][35][36]. The predictions of A W ± L [15-21, 37, 38] are given, and it is found that the higher order QCD corrections are small [39][40][41][42]. Especially in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some theoretical studies on A W ± L based on available extractions or parametrizations of quark helicity distributions [33][34][35][36]. The predictions of A W ± L [15-21, 37, 38] are given, and it is found that the higher order QCD corrections are small [39][40][41][42]. Especially in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in Ref. [42], the analytic expressions for the spin-dependent asymmetries at next-to-leading order are given and the calculated results with sea quark helicity distributions from different groups are compared with the experimental data [30]. It is found that the data prefer a rather sizable positive valued ∆ū.…”
Section: Introductionmentioning
confidence: 99%
“…The observed positron and electron pseudorapidities, η e , are related to y W and to the decay angle of the positron and electron in the W rest frame [19]. Higher-order corrections to A L (η e ) are known [20][21][22] and have been incorporated into the aforementioned global analyses.…”
mentioning
confidence: 99%
“…These results are shown in Fig. 2 with two theoretical calculations: (CHE) [21] for the NNPDFpol1.1 [14] and a recent calculation [31] using the DSSV 14 PDF sets [32]. While the DSSV 14 curve was obtained from a global fit of DIS and SIDIS data (including recent COMPASS results [15,16]), the NNPDFpol1.1 uncertainty band contains the 2012 STAR [11] result for flavor separation in addition to DIS data.…”
mentioning
confidence: 99%
“…To calculate the 2013 positive and negative η bin asymmetries a generalized form for these equations was used. The green line and shaded region shows a theoretical calculation using CHE [21] with the NNPDFpol1.1 PDF sets [14], while the dashed magenta line shows the DSSV14 calculation [31].…”
mentioning
confidence: 99%